First Impression Misleads Emotion Recognition - Colonnello, Valentina; Russo, Paolo Maria; Mattarozzi, Katia (Frontiers in Psychology, 2019)
Recognition of others’ emotions is a key life ability that guides one’s own choices and behavior, and it hinges on the recognition of others’ facial cues. Independent studies indicate that facial appearance-based evaluations affect social behavior, but little is known about how facial appearance–based trustworthiness evaluations influence the recognition of specific emotions. We tested the hypothesis that first impressions based on facial appearance affect the recognition of basic emotions. A total of 150 participants completed a dynamic emotion recognition task. In a within-subjects design, the participants viewed videos of individuals with trustworthy-looking, neutral, or untrustworthy-looking faces gradually and continuously displaying basic emotions (happiness, anger, fear, and sadness). The participants accuracy and speed in recognizing the emotions were measured. Untrustworthy-looking faces decreased participants’ emotion recognition accuracy and speed, across emotion types. In addition, faces that elicited a positive inference of trustworthiness enhanced emotion recognition speed of fear and sadness, emotional expressions that signal another’s distress and modulate prosocial behavior. These findings suggest that facial appearance–based inferences may interfere with the ability to accurately and rapidly recognize others’ basic emotions.